Specular reflection of neutrons at phospholipid monolayers. Changes of monolayer structure and headgroup hydration at the transition from the expanded to the condensed phase state. - Bayerl, T; Thomas, R; Penfold, J; Rennie, A; Sackmann, E (1990)
The specular neutron reflection technique has been applied for the first time to study the structure and head group hydration of a phospholipid monolayer (dimyristoylphosphatidylcholine containing negatively charged phospholipids) in the condensed and expanded state. By variation of the contrast of the subphase to that of the air it is shown that at the transition from the condensed to the expanded state the carboxyl bonds of the glycerol backbone are hydrated leading to a strong structural change of the headgroup. The total monolayer thickness in the condensed state is 22.5 +/- 1 A (tilt angle 32 +/- 6 degrees) and decreases to 19.5 +/- 1 A in the expanded state. The mean molecular volume increases from 1190 +/- 50 A3 to 1250 +/- 50 A3.